The catalytically inactive tyrosine phosphatase HD-PTP/PTPN23 is a novel regulator of SMN complex localization - Husedzinovic, Alma; Reymann, Jürgen; Dräger-Meurer, Stefanie; Erfle, Holger; Gruss, Oliver (Molecular biology of the cell, 2015)
The survival motor neuron (SMN) complex fulfils essential functions in the assembly of snRNPs, which are key components in the splicing of pre-mRNAs. Little is known about the regulation of SMN complex activity by posttranslational modification despite its complicated phosphorylation pattern. Several phosphatases had been implicated in the regulation of SMN, including the nuclear phosphatases PPM1G and PP1γ. Here we systematically screened all human phosphatase gene products for a regulatory role in the SMN complex. We used the accumulation of SMN in Cajal bodies of intact proliferating cells, which actively assemble snRNPs, as a readout for unperturbed SMN complex function. Knockdown of 29 protein phosphatases interfered with SMN accumulation in Cajal bodies, suggesting impaired SMN complex function, among those the catalytically inactive, non-receptor-type tyrosine phosphatase PTPN23/HD-PTP. Knockdown of PTPN23 also led to changes in the phosphorylation pattern of SMN without affecting the assembly of the SMN complex. We further show interaction between SMN and PTPN23 and document that PTPN23, like SMN, shuttles between nucleus and cytoplasm. Our data provide the first comprehensive screen for SMN complex regulators and establish a novel regulatory function of PTPN23 in maintaining a highly phosphorylated state of SMN, which is important for its proper function in snRNP assembly.